Accommodating inappropriate language: how students react to the translation of inappropriate language in the classroom - Tracey Simpson (Anglophonia)
Based on experiences in the classroom, this paper examines some of the issues associated with using swearwords for academic exercises and in authentic communication situations. Within societies, politeness and impoliteness are extremely coded and so there is a natural tendency for native speakers to accommodate people and social conventions by not using certain words. However, the use of words considered as taboo is problematic for non-native speakers; they are consequently reduced to a system of trial and error at their own peril. We may then ask ourselves how taboo words are perceived by students and what place they have in the classroom. A study was carried out with students from undergraduate through to postgraduate levels; specific data were collected with a questionnaire and a translation exercise. An analysis of the results showed two contrasting reactions when faced with the translation of swearwords: students are either reticent and refrain from using the most suitable word in the target language (over-accommodation) or they suggest expressions that are unnaturally over-offensive (absence of accommodation). In both cases, the students’ answers were inadequate. Reasons are suggested to explain these different attitudes and results.